IMPROVING DIGITAL MARKETING FOR MICRO ENTERPRISES IN SEGORO TAMBAK VILLAGE: A COMMUNITY ENGAGEMENT - Gilbert, Warren; Suyanto, Suyanto (As-Sidanah, 2025)
Digital marketing is an essential strategy for microenterprises to expand market share and increase sales. To support micro enterprises in Segoro Tambak Village, Sedati Subdistrict, Sidoarjo Regency, a community engagement program was implemented through the national grant. The program involved preliminary observations, digital marketing workshops, interviews, hands-on training, mentoring, and follow-up activities. As part of the intervention, Instagram and TikTok accounts were created for 20 micro enterprises, enabling them to showcase their products and reach broader audiences. Pre- and post-program assessments indicated significant improvements: over 73% of participants reported increased confidence in using social media, while 75% successfully uploaded promotional content independently after mentoring. Two key outcomes emerged from the engagement: (1) the establishment of social media accounts for both the village group and individual micro firms, and (2) enhanced knowledge and digital literacy among participants, particularly those previously unfamiliar with smartphone-based marketing. These results demonstrate how structured community-based interventions can effectively bridge the digital divide, empower local entrepreneurs, and increase product visibility and sales. Beyond immediate benefits, this initiative contributes to the long-term sustainability and competitiveness of micro enterprises in adapting to the rapidly evolving digital economy.